Evaluation of a university seminar on the use of digital media in the physics classroom - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Journal of Physics: Conference Series)
Abstract Fostering digital competencies is an important aspect of pre-service teacher education. However, for physics, there is a lack of systematically surveyed and evidence-based seminars that specifically take into account relevant research findings. Thus, we developed a research-based seminar on the effective use of digital media in physics classrooms and investigated its effects on pre-service teachers (PSTs) professional competencies in a mixed-methods design. Our quantitative analyses of different competence components surveyed in a pre-post-design indicate that the seminar leads to an increase in motivation to use digital media in the physics classroom. Nevertheless, no significant increase in digital-media PCK was found, which could be due to the small sample. The seminar design, however, was predominantly evaluated positively by experts and PSTs in guided interviews. Based on the results, it is planned to further refine the original seminar using a Design-Based Research approach.

Evaluation of a university seminar on the use of digital media in the physics classroom - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Journal of Physics: Conference Series)
Abstract Fostering digital competencies is an important aspect of pre-service teacher education. However, for physics, there is a lack of systematically surveyed and evidence-based seminars that specifically take into account relevant research findings. Thus, we developed a research-based seminar on the effective use of digital media in physics classrooms and investigated its effects on pre-service teachers (PSTs) professional competencies in a mixed-methods design. Our quantitative analyses of different competence components surveyed in a pre-post-design indicate that the seminar leads to an increase in motivation to use digital media in the physics classroom. Nevertheless, no significant increase in digital-media PCK was found, which could be due to the small sample. The seminar design, however, was predominantly evaluated positively by experts and PSTs in guided interviews. Based on the results, it is planned to further refine the original seminar using a Design-Based Research approach.

Compact, High-Speed Mach-Zehnder Modulator with On-Chip Linear Drivers in Photonic BiCMOS Technology - Kress, Christian; Schwabe, Tobias; Rhee, Hanjo; Scheytt, J. Christoph (IEEE Access)

Randomised material parameter impedance dataset of piezoelectric rings - Koch, Kevin; Friesen, Olga; Claes, Leander

Randomised material parameter piezoelectric impedance dataset with structured electrodes - Koch, Kevin; Claes, Leander

Analysis of Inverter Operation Modes of an IGBT-Based ZCS LLC Converter for a 2 kW Automotive On-Board DC-DC - Urbaneck, Daniel; Wiegard, Jan; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Study on Sample Geometries for Ferrite Characterisation in the MHz-Range - Piepenbrock, Till; Keuck, Lukas; Schachten, Sebastian; Böcker, Joachim; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Pitfalls and their Avoidability in the Double-Pulse Test - Förster, Nikolas; Urbaneck, Daniel; Kohlhepp, Benedikt; Kübrich, Daniel; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

FEM Modelling of Dimensional-Resonant Inductors for LLC Converters in MHz Range - Piepenbrock, Till; Schafmeister, Frank; Böcker, Joachim (SPEEDAM 2024; 27th International Symposium on Power Electronics, Electrical Drives, Automation and Motion)

Experimentally Verified 22 kW, 30 kHz LLC Resonant Converter Design with new Control for a 1 MW Cascaded H-Bridge Converter - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (ECCE Europe 2024; IEEE Energy Conversion Congress & Exposition Europe)

Inklusion verstehen - Szenen aus dem Unterricht in interdisziplinärer Reflexion
Die Verankerung von Inklusion als Querschnittsthema lehramtsbezogener Studiengänge fordert zu einer interdisziplinären Verständigung über die Vorstellung inklusiver Unterrichtsgestaltung heraus. Die ForscherInnengruppe der Universität Paderborn wählt hierfür als methodischen Ausgangspunkt Vignetten als verdichtete Fallbeispiele aus der Unterrichtspraxis, die aus verschiedenen fachübergreifenden praxistheoretischen Perspektiven gelesen und so gemeinsam diskutiert werden. In der Linie praxistheoretischer Arbeiten reflektiert das Buch Praktiken im inklusiven Fachunterricht in der Spannung zu den normativen (sonder-)pädagogischen bzw. (fach-)didaktischen Vorannahmen, um aus dieser Reflexion eigenes verantwortetes Handeln zu entwickeln. Die Vignettenbündel laden so zum diskursiven Austausch, zur Kontrastierung oder zum "Einfangen" selbst erlebter Unterrichtspraxen auf dem Weg des Verstehens von Inklusion in Theorie und Praxis ein.

ESLM: Improving Entity Summarization by Leveraging Language Models - Firmansyah, Asep Fajar; Moussallem, Diego; Ngomo, Axel-Cyrille Ngonga (The Semantic Web)

The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults - Revheim, Ingrid; Ballance, Simon; Standal, Adelheid Fretland; Rieder, Anne; Dierkes, Jutta; Buyken, Anette; Gilja, Odd Helge; Hausken, Trygve; Rosendahl-Riise, Hanne (Nutrition & Metabolism)
Abstract Background The cereal fibre β-glucan reduces postprandial glycaemia, however, the underlying mechanisms are not fully understood. Thus, the aim of this study was to investigate the acute effect of a β-glucan-enriched oat bread on gastric emptying half-time ( T 1/2 ), gastric emptying lag phase ( T lag ), and gastric emptying rate (GER), and the secretion of glucagon-like peptide-1 (GLP-1) as potential means to influence postprandial glycaemia. Methods A randomised crossover trial was conducted in 22 healthy adults (age 24.6 ± 3.1 years, BMI 23.1 ± 2.7 kg/m 2 ) receiving 25 g available carbohydrates from a β-glucan-enriched oat bread or a control whole-wheat bread at two non-consecutive days. T 1/2 , T lag , and GER were determined based on ultrasound measures of the cross-sectional gastric antrum area in the fasting state and 15, 30, 45, 60, 90, and 120 min postprandially. Capillary glucose, serum insulin, and plasma GLP-1 concentrations were measured at the same time points. Results A biphasic pattern of gastric emptying with a distinct T lag before the commencement of emptying was observed in most subjects for both bread types. While no differences in GER were evident ( p = 0.562), consumption of the oat bread significantly increased T 1/2 by 18 min and T lag by 14 min compared with the whole-wheat bread ( p = 0.005 and p = 0.010, respectively). In addition, the oat bread significantly reduced iAUC 2h for glucose and insulin responses compared with the whole-wheat bread ( p = 0.001 and p < 0.001, respectively). There were no significant differences in GLP-1 response between the two breads ( p = 0.892). Conclusion The increased T 1/2 and T lag could offer a potential mechanism for the observed attenuation of postprandial glycaemia and insulinemia after consumption of the β-glucan-enriched oat bread compared with the whole-wheat bread. Trial registration : The study is registered at clinicaltrails.gov (NCT04571866).

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Nutri-Score 2023 update - Merz, Benedikt; Temme, Elisabeth; Alexiou, Hélène; Beulens, Joline Wilhelma Johanna; Buyken, Anette; Bohn, Torsten; Ducrot, Pauline; Falquet, Marie-Noëlle; Solano, Marta García; Haidar, Hanna; Infanger, Esther; Kühnelt, Charlotte; et al. (Nature Food)

Security Analysis of BigBlueButton and eduMEET - Heitmann, Nico; Siewert, Hendrik; Moog, Sven; Somorovsky, Juraj (Applied Cryptography and Network Security)
Video conferencing systems have become an indispensable part of our world. Using video conferencing systems implies the expectation that online meetings run as smoothly as in-person meetings. Thus, online meetings need to be just as secure and private as in-person meetings, which are secured against disruptive factors and unauthorized persons by physical access control mechanisms. To show the security dangers of conferencing systems and raise general awareness when using these technologies, we analyze the security of two widely used research and education open-source video conferencing systems: BigBlueButton and eduMEET. Because both systems are very different, we analyzed their architectures, considering the respective components with their main tasks, features, and user roles. In the following systematic security analyses, we found 50 vulnerabilities. These include broken access control, NoSQL injection, and denial of service (DoS). The vulnerabilities have root causes of different natures. While BigBlueButton has a lot of complexity due to many components, eduMEET, which is relatively young, focuses more on features than security. The sheer amount of results and the lack of prior work indicate a research gap that needs to be closed since video conferencing systems continue to play a significant role in research, education, and everyday life.

Wirtschafts- und Finanzpolitik als Schlüsselbereiche europäischer Einigung - Schönhärl, Korinna; Leucht, Brigitte (Europäische Einigung zwischen Anspruch und Wirklichkeit. Eine historische Bestandsaufnahme)
Im Gespräch loten Brigitte Leucht und Korinna Schönhärl aus, welche Rolle wirtschafts- und finanzpolitische Überlegungen und Faktoren für den europäischen Einigungsprozess gespielt haben und immer noch spielen.
Keywords: Wirtschaftsgeschichte; Europäische Geschichte; Europäische Einigung; Staatsverschuldung; Moderne griechische Geschichte

Utilizing Description Logics for Global Explanations of Heterogeneous Graph Neural Networks - Köhler, Dominik; Heindorf, Stefan (arXiv:2405.12654)
Graph Neural Networks (GNNs) are effective for node classification in graph-structured data, but they lack explainability, especially at the global level. Current research mainly utilizes subgraphs of the input as local explanations or generates new graphs as global explanations. However, these graph-based methods are limited in their ability to explain classes with multiple sufficient explanations. To provide more expressive explanations, we propose utilizing class expressions (CEs) from the field of description logic (DL). Our approach explains heterogeneous graphs with different types of nodes using CEs in the EL description logic. To identify the best explanation among multiple candidate explanations, we employ and compare two different scoring functions: (1) For a given CE, we construct multiple graphs, have the GNN make a prediction for each graph, and aggregate the predicted scores. (2) We score the CE in terms of fidelity, i.e., we compare the predictions of the GNN to the predictions by the CE on a separate validation set. Instead of subgraph-based explanations, we offer CE-based explanations.

Knowledge Management for Service and Maintenance on the Distribution Grid—Conceptualizing an Assistance System based on a Large Language Model Wissensmanagement für Wartung und Instandhaltung im Verteilnetz – Konzeption eines Assistenzsystems basierend auf einem Large Language Model - zur Heiden, Philipp; Kaltenpoth, Sascha (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung Verteilnetzbetreiber in Deutschland stehen vor großen Herausforderungen bei dem Management ihres unternehmensspezifischen Wissens: Mitarbeiterengpässe durch den demographischen Wandel, Wissen ist nur implizit vorhanden und nicht in Wissensmanagementsystemen digitalisiert, teilweise gibt es gar keine Wissensmanagementsysteme oder Konzepte und das Verteilnetz wird immer komplexer. Verbunden mit zunehmender Belastung von zentralen Komponenten im Verteilnetz durch die Energiewende bedarf es neuer Lösungen, besonders für die wissensintensiven Wartungs- und Instandhaltungsprozesse. Generative Artificial Intelligence als aufstrebende Technologie, insb. durch Large Language Models, zeigt hier erste Erfolge für die Anleitung, Entscheidungsunterstützung und den Wissenstransfer. Aufbauend auf dem Design Science Research Forschungsparadigma wird in diesem Beitrag ein ganzheitlicher Ansatz des Wissensmanagements konzipiert, welcher als zentrale Komponente auf einem Assistenzsystem basiert. Ein Large Language Model generiert Hilfestellungen für Netzmonteure während der Wartung und Instandhaltung auf Basis von Anleitungen. Neben der Konzeption zeigt dieser Beitrag auch die erarbeitete Strategie zur Demonstration und zukünftigen Evaluation der Ergebnisse. Der Beitrag liefert ein für Verteilnetzbetreiber neuartiges Konzept Large Language Model basierter Assistenzsysteme zum Wissensmanagement und zeigt zudem nachgelagerte Schritte auf, die vor einer Markteinführung notwendig sind.

Flexible operation and integration of high-temperature heat pumps using large temperature glides - Knorr, Lukas; Schlosser, Florian; Horstmann, Nils; Divkovic, Denis; Meschede, Henning (Applied Energy)

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Soziale Grenzen und Grenzbearbeitungen. Ein Zugang zur sozialwissenschaftlichen Bildungsforschung - Haker, Christoph; Otterspeer, Lukas (Bildungsforschung: Erziehungswissenschaftliche Perspektiven)
Der Beitrag führt in die von uns verfolgte Forschungsperspektive der sozialen Grenzen und Grenzbearbeitungen ein und bringt diese mit den Begriffen Bildung und Bildungsforschung zusammen. Unsere Theoretisierung beginnt mit einem sozialtheoretisch unterbestimmten Verständnis sozialer Grenzen und Grenzbearbeitungen. Dieses erhebt einerseits den Anspruch, nah an Alltagserfahrungen mit sozialen Grenzen und Grenzbearbeitungen zu sein. Andererseits ermöglicht es den Einstieg in ganz unterschiedliche Sozialtheorien und damit eine multiperspektivische Forschungspraxis. Dieses Potential plausibilisieren wir am Beispiel von Analysen zu Fragestellungen der Wissenschafts- und Rechtsextremismusforschung, die wir selbst durchgeführt haben. Für Bildung und Bildungsforschung sind in diesem Zusammenhang der Blick auf Bildungsprozesse, Bildungsinstitutionen und die Konzeption von Forschung als eine selbstreflexive Bildungspraxis relevant.

Tailored metrics for assessing the quality of MBSE models - Gräßler, Iris; Wiechel, Dominik; Özcan, Deniz; Taplick, Patrick (Proceedings of the Design Society)
Abstract System models are used to merge relevant engineering artefacts and relationships. Therefore, a high model quality must be ensured. Currently, there is no method for defining company-specific metrics to assess system model quality. In a six-step research approach, a method is defined: (1) literature analysis on quality assessment approaches, (2) derivation of success factors, (3) evaluation of approaches, (4) development of a method, (5) application in automotive industry, and (6) evaluation. The method supports system engineers to derive tailored metrics to objectively assess the model quality.

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

Doing language im Deutschunterricht. Eine Analyse sprachbezogener Adressierungen in diskursiver Praxis - Büttner, Denise
Die Studie leistet einen empirisch-rekonstruktiven Beitrag zu einer machtkritisch ausgerichteten Fachdidaktik. Sie fokussiert den Deutschunterricht und die darin stattfindenden Interaktionen als diskursive Praxis, in der ein spezifisches Wissen in, über und angesichts von Sprache relevant gemacht wird. Für Subjektivierung ist jenes Wissen hochgradig wirkmächtig und bleibt den Akteur*innen im Prozess der schulischen Enkulturation doch größtenteils unbewusst. Darin liegt ein hohes Potential für die institutionelle (Re-)Produktion von Linguizismus.Vor diesem Hintergrund eröffnet die Studie einen Blick auf sprachbezogene Adressierungen, die in charakteristischer Weise vom Fach selbst ausgehen. Sie werden in (fach)didaktischen und pädagogischen Programmatiken breit kommuniziert und zeichnen sich bis auf die Ebene unterrichtlicher Praktiken ab. Um das Zusammenspiel von fachspezifischer Adressierung und Praktiken des ‚doing language‘ möglichst eng aufeinander beziehen und in rekonstruktionslogisch plausibilisierte Zusammenhänge bringen zu können, liegt der Arbeit ein wissenssoziologisch-diskursanalytischer Ansatz zugrunde.
Keywords: Diskursanalyse; Machtkritik; Sprache und Bildung; Rekonstruktive Unterrichtsforschung; Subjektivierung; Fachdidaktik

Soziotechnisches Risikomanagement als Erfolgsfaktor für die Digitale Transformation - Menzefricke, Jörn Steffen; Gabriel, Stefan; Gundlach, Thomas; Hobscheidt, Daniela; Kürpick, Christian; Schnasse, Felix; Scholtysik, Michel; Seif, Heiko; Koldewey, Christian; Dumitrescu, Roman (Digitalisierung. Fallstudien, Tools und Erkenntnisse für das digitale Zeitalter)

Dimensioning and Lifetime Prediction Model for a Hybrid, Hydrogen-Based Household PV Energy System Using Matlab/Simulink - Möller, Marius Claus; Krauter, Stefan (Solar)
This paper presents a model of an energy system for a private household extended by a lifetime prognosis. The energy system was designed for fully covering the year-round energy demand of a private household on the basis of electricity generated by a photovoltaic (PV) system, using a hybrid energy storage system consisting of a hydrogen unit and a lithium-ion battery. Hydrogen is produced with a Proton Exchange Membrane (PEM) electrolyser by PV surplus during the summer months and then stored in a hydrogen tank. Mainly during winter, in terms of lack of PV energy, the hydrogen is converted back into electricity and heat by a fuel cell. The model was created in Matlab/Simulink and is based on real input data. Heat demand was also taken into account and is covered by a heat pump. The simulation period is a full year to account for the seasonality of energy production and demand. Due to high initial costs, the longevity of such an energy system is of vital interest. Therefore, this model was extended by a lifetime prediction in order to optimize the dimensioning with the aim of lifetime extension of a hydrogen-based energy system. Lifetime influencing factors were identified on the basis of a literature review and were integrated in the model. An extensive parameter study was performed to evaluate different dimensionings regarding the energy balance and the lifetime of the three components, electrolyser, fuel cell and lithium-ion battery. The results demonstrate the benefits of a holistic modelling approach and enable a design optimization regarding the use of resources, lifetime and self-sufficiency of the system

Simulation-based investigation of the metrological interface structural resolution capability of X-ray computed tomography scanners - Busch, Matthias; Hausotte, Tino (Journal of Sensors and Sensor Systems)
Abstract. The miniaturisation of components leads to new demands on measurement systems. One of these is the resolution. As a volumetric analysis method and method of non-destructive testing, industrial X-ray computed tomography (XCT) has the ability to measure geometrical features and their corresponding dimensions without destroying them and can therefore be used for quality assurance. However, the concept of resolution is not trivial for XCT and has not yet been finally clarified. In particular, the interface structural resolution, the detectability of two surfaces facing each other after surface segmentation, faces a lack of a test specimen, a corresponding measurand and a reliable method. Simulation-based XCT investigations of a method to determine this type of resolution are presented in this article using the geometry of a test specimen that contains several radially arranged holes of the same size. The borehole diameters correspond to the distance between the holes to investigate the resolvability of surfaces and interfaces. The evaluation is based on mean and extreme values of grey value profiles between the individual boreholes of the reconstructed volume. It is shown that the geometrical detectability of the test specimen surface and interface can be extended by a reasonable choice of the threshold value for surface segmentation within a defined interval. With regard to the resolving capability, a distinction is made between assured detectability and possible detectability, as well as the threshold value used when using the ISO50 threshold for surface segmentation and measurement chain completion.
Keywords: Electrical and Electronic Engineering; Instrumentation

Practice-Oriented Research in Tertiary Mathematics Education

Are Neural Bug Detectors Comparable to Software Developers on Variable Misuse Bugs? - Richter, Cedric; Haltermann, Jan Frederik; Jakobs, Marie-Christine; Pauck, Felix; Schott, Stefan; Wehrheim, Heike (37th IEEE/ACM International Conference on Automated Software Engineering)

Benchmark Fuzzing for Android Taint Analyses - Schott, Stefan; Pauck, Felix (2022 IEEE 22nd International Working Conference on Source Code Analysis and Manipulation (SCAM))

Scaling Arbitrary Android App Analyses - Pauck, Felix (37th IEEE/ACM International Conference on Automated Software Engineering)

Experimentelle Kompetenz Physikstudierender - Bauer, Anna Brigitte
Für den Erwerb fachmethodischer Fähigkeiten stellen Laborpraktika eine zentrale Lerngelegenheiten des Physikstudiums dar. Trotz ihrer hohen Bedeutung fehlt ein hochschulfachdidaktischer Diskurs zu einer lehr-lerntheoretischen Fundierung. Zudem wird ihre Lernwirksamkeit aufgrund der bestehenden didaktischen Gestaltung kritisiert. Die weit verbreiteten engmaschigen Aufgabenstellungen enthalten keine Anreize zur tiefergehenden Auseinandersetzung mit den Inhalten. Um der Diskrepanz zwischen den Zielsetzungen und den von den Lernenden erworbenen Fähigkeiten entgegenzuwirken, liegen aktuell nur wenige und zudem nur punktuelle Grundlagen für eine evidenzbasierte Überarbeitung dieses Veranstaltungsformates vor. Ziel dieser Arbeit ist daher, einen Vorschlag für ein performanzorientiertes Kompetenzstrukturmodell auf universitärem Niveau zu entwickeln, das die Inhaltsbereiche, die experimentellen Fähigkeiten und Fertigkeiten sowie die Qualitätsausprägungen experimenteller Handlungen systematisiert.Die Modellierung ist auf Basis der Analyse videografierter experimenteller Performanz von 16 unterschiedlich fähigen Proband:innen realisiert worden. Für die Entwicklung der Dimensionen Fachmethodik und Qualitätsausprägung werden unter Nutzung der qualitativen Forschungsansätze Dokumentarische Methode und Typenbildung die charakteristischen Merkmale universitären Experimentierens identifiziert und anschließend systematisiert. Zur Prüfung der Passung des Modells zur Perspektive der Wissenschaft Physik ist ein Interrating mit einem Fachwissenschaftler durchgeführt worden, das sehr gute Übereinstimmungswerte liefert. Die Passung des Modells zur Perspektive der Praktikumsleiter:innen ist durch ein Expertenrating erfolgt. Ein Rangfolgen-Vergleich zeigt hohe Übereinstimmungswerte.

Supporting Business Model Decision-making in B2B Ecosystems: A Framework for Using System Dynamics - Ksouri-Gerwien, C.; Vorbohle, Christian (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Anrisserkennung an geclinchten Proben während einer zyklischen Belastung unter Nutzung eines Scanning Laser Doppler Vibrometers - Brosius, Alexander; Ewenz, Lars; Stephan, Richard; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Ableitung flacher Probengeometrien zur Abbildung mehraxialer Spannungszustände in Clinchverbindungen unter zyklischer Beanspruchung - Ewenz, Lars; Kuczyk, Martin; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Untersuchungen zum Geometrie- und Frequenzeinfluss bei der Ermittlung zyklischer Kennwerte geclinchter Überlappverbindungen - Ewenz, Lars; Kühne, R.; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Consistent Optical and Electrical Noise Figure - Noé, Reinhold (Journal of Lightwave Technology)

Die Schrift entHeiligen. Praktisch-theologische Überlegungen zum Bibelgebrauch als Transformation des Heiligen - Schroeter-Wittke, Harald (Heilige Schriften in der Kritik. XVII. Europäischer Kongress für Theologie (5.-8. September 2021 in Zürich). VWGTh 68)

Updatable Privacy-Preserving Reputation System based on Blockchain - Pilot, Matthias

Die mündliche Prüfung. Eine Einführung - Matz, Frauke; Rogge, Michael; Rumlich, Dominik

Mechatronik und elektrische Antriebe / Mechatronics and electrical drives - Böcker, Joachim

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Predicting the Bond Quality of Heavy Copper Wire Bonds using a Friction Model Approach - Althoff, Simon
Ultraschall-Drahtbonden ist eine Standardtechnologie im Bereich der Aufbau- und Verbindungstechnik von Leistungshalbleitermodulen. Um Prozessschritte und damit wertvolle Zeit zu sparen, sollen die Kupferdickdrähte für die Leistungshalbleiter auch für die Kontaktierung von eingespritzten Anschlusssteckern im Modulrahmen verwendet werden. Das Kontaktierungsverfahren mit diesen Drähten auf Steckern in dünnwandigen Kunststoffrahmen führt häufig zu unzureichender Bondqualität. In dieser Arbeit wird das Bonden von Anschlusssteckern experimentell und anhand von Simulationen untersucht, um die Prozessstabilität zu steigern. Zunächst wurden Experimente auf Untergründen mit hoher Steifigkeit durchgeführt, um Störgrößen von Untergrundeigenschaften zu verringern. Die gewonnenen Erkenntnisse erlaubten die Entwicklung eines Simulationsmodells für die Vorhersage der Bondqualität. Dieses basiert auf einer flächenaufgelösten Reibarbeitsbestimmung im Fügebereich unter Berücksichtigung des Ultraschallerweichungseffektes und der hierdurch entstehenden hohen Drahtverformung. Experimente an den Anschlusssteckern im Modulrahmen zeigten eine verringerte Relativverschiebung zwischen Draht und Stecker, was zu einer deutlichen Verringerung der Reibarbeit führt. Außerdem wurden verminderte Schwingamplituden des Bondwerkzeugs nachgewiesen. Dies führt zu einer weiteren Reduktion der Reibarbeit. Beide Effekte wurden mithilfe eines Mehrmassenschwingers modelliert. Die gewonnenen Erkenntnisse und die erstellten Simulationsmodelle ermöglichen die Entwicklung von Klemmvorrichtungen, welche die identifizierten Störgrößen gezielt kompensieren und so ein verlässliches Bonden der Anschlussstecker im gleichen Prozessschritt ermöglichen, in dem auch die Leistungshalbleiter kontaktiert werden.
Keywords: heavy copper bonding; wire bonding; quality prediction; friction model; point-contact-element

Modellierung und Optimierung reibungsbasierter Ultraschall-Pulvertransportprozesse - Dunst, Paul
Der Transport feiner Pulver mit in der Regel sehr hohen adhäsiven und kohäsiven Eigenschaften stellt für viele konventionelle Transportsysteme eine große Herausforderung dar. Durch die Anwendung von Ultraschallschwingungen können insbesondere die hohen adhäsiven Kontaktkräfte und damit auch die Reibungseigenschaften manipuliert werden. Ein neu entwickeltes Pulvertransportsystem nutzt Ultraschallschwingungen, um die effektiven Tangentialkräfte im Pulver-Rohrkontakt zu reduzieren. Durch den koordinierten Einsatz von Ultraschallpulsen während einer niederfrequenten harmonischen Axialschwingung des Transportrohres wird ein kontinuierlicher Pulvertransport ermöglicht. Nach einer Einführung in die Grundlagen der Reibung und Reibungsmanipulation von Festkörpern und Pulvern sowie der Charakterisierung von Pulvern wird das Pulvertransportsystem auf Basis der Reibungsmanipulation inklusive der Leistungselektronik und der Ansteuerungshardware vorgestellt. Eine Sensitivitätsanalyse zeigt, dass die Anregungsparameter des Pulvertransportsystems ein großes Optimierungspotential aufweisen. Es wird ein effizientes, modulares Modell des Pulvertransportsystems vorgestellt, welches neben dem eigentlichen Modell des Transportprozesses ein Modell der Rohrschwingung und ein kennlinienbasiertes Modell des Pulver-Rohrkontakts beinhaltet. Mithilfe des Modells des Pulvertransportsystems werden Anregungsparameter hinsichtlich Amplituden und Frequenzen der auftretenden Schwingungen sowie der Schaltzeiten des Ultraschallpulses optimiert.
Keywords: Ultraschall; Pulvertransport; Modellierung; Optimierung; Reibung; Adhäsion; Kohäsion; Reibungsmanipulation

A Unifying Approach to Efficient (Near-)Gathering of Disoriented Robots with Limited Visibility - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Proceedings of the 26th International Conference on Principles of Distributed Systems (OPODIS))

Quantum space, ground space traversal, and how to embed multi-prover interactive proofs into unentanglement - Gharibian, Sevag; Rudolph, Dorian (14th Innovations in Theoretical Computer Science (ITCS))
Savitch's theorem states that NPSPACE computations can be simulated in PSPACE. We initiate the study of a quantum analogue of NPSPACE, denoted Streaming-QCMASPACE (SQCMASPACE), where an exponentially long classical proof is streamed to a poly-space quantum verifier. Besides two main results, we also show that a quantum analogue of Savitch's theorem is unlikely to hold, as SQCMASPACE=NEXP. For completeness, we introduce Streaming-QMASPACE (SQMASPACE) with an exponentially long streamed quantum proof, and show SQMASPACE=QMA_EXP (quantum analogue of NEXP). Our first main result shows, in contrast to the classical setting, the solution space of a quantum constraint satisfaction problem (i.e. a local Hamiltonian) is always connected when exponentially long proofs are permitted. For this, we show how to simulate any Lipschitz continuous path on the unit hypersphere via a sequence of local unitary gates, at the expense of blowing up the circuit size. This shows quantum error-correcting codes can be unable to detect one codeword erroneously evolving to another if the evolution happens sufficiently slowly, and answers an open question of [Gharibian, Sikora, ICALP 2015] regarding the Ground State Connectivity problem. Our second main result is that any SQCMASPACE computation can be embedded into "unentanglement", i.e. into a quantum constraint satisfaction problem with unentangled provers. Formally, we show how to embed SQCMASPACE into the Sparse Separable Hamiltonian problem of [Chailloux, Sattath, CCC 2012] (QMA(2)-complete for 1/poly promise gap), at the expense of scaling the promise gap with the streamed proof size. As a corollary, we obtain the first systematic construction for obtaining QMA(2)-type upper bounds on arbitrary multi-prover interactive proof systems, where the QMA(2) promise gap scales exponentially with the number of bits of communication in the interactive proof.

Interaktive Einkaufserlebnisse in Innenstädten

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens: Theorie, Methodik und Einblicke in die Vergänglichkeit)